Effect of ACL graft material on anterior knee force during simulated in vivo ovine motion applied to the porcine knee: An in vitro examination of force during 2000 cycles. Issue 12 (15th July 2015) - Boguszewski, Daniel V.; Wagner, Christopher T.; Butler, David L.; Shearn, Jason T.
ABSTRACT: This study determined how anterior cruciate ligament (ACL) reconstruction affected the magnitude and temporal patterns of anterior knee force and internal knee moment during 2000 cycles of simulated gait. Porcine knees were tested using a six degree‐of‐freedom robot, examining three porcine allograft materials compared with the native ACL. Reconstructions were performed using: (1) bone‐patellar tendon‐bone allograft (BPTB), (2) reconstructive porcine tissue matrix (RTM), or (3) an RTM‐polymer hybrid construct (Hybrid). Forces and moments were measured over the entire gait cycle and contrasted at heel strike, mid stance, toe off, and peak flexion. The Hybrid construct performed the best, as magnitude and temporal changes in both anterior knee force and internal knee moment were not different from the native ACL knee. Conversely, the RTM knees showed greater loss in anterior knee force during 2000 cycles than the native ACL knee at heel strike and toe off, with an average force loss of 46%. BPTB knees performed the least favorably, with significant loss in anterior knee force at all key points and an average force loss of 61%. This is clinically relevant, as increases in post‐operative knee laxity are believed to play a role in graft failure and early onset osteoarthritis. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1789–1795, 2015.